Information technology in organizations emerging issues in ethics and policy - Sviokla, John J. (Harvard Business School, 1990)
Introduces a framework for identifying and analyzing the ethical and policy issues triggered by the various capabilities of information technology (IT). Ten IT capabilities are defined (access, capture, speed, permanence/storage. duplication, tracking, monitoring, data recombination, job redesign, and supplier power) and mapped against five managerial issues they can trigger (privacy, ownership, control, accuracy, and security). These five issues are then mapped against four policy areas that might address them (data policy, intellectual property rights, worker's rights, and competitiveness). Key questions are raised and various examples of IT's impact on managerial decision making are presented. Finally, four models of ethical analysis are suggested as possible tools for approaching these managerial choices: stakeholder analysis, utilitarian goal-based analysis, rights-based analysis, and duty-based analysis. Useful in an introduction to the management of IT, as well as in a business ethics course.